Charakter prawny odpowiedzialności członków zarządu spółki z o.o. za cywilnoprawne zobowiązania spółki na podstawie art. 299 Kodeksu spółek handlowych - Nowak, Aleksandra (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The construction of Article 299 of the Code of Commercial Companies demonstrates that in order to hold the management board liable, it is sufficient for the creditor to demonstrate the existence of the obligation and the ineffectiveness of execution against the company. Hence, the board members responsibility appears as a liability under guarantee. On the other hand, conditions under which member of the board can absolve himself thereof imply delictual character of the liability. Consequently, legal nature of the liability of members of a Management Board of a limited liability company for the company’s civil obligations, notwithstanding the firm stance taken by the Supreme Court, remains subject to major controversy. It is therefore – nearly 10 years since the Supreme Court’s conclusive rulling on the matter – high time to to adress the aforementioned issues by reformulating conclusions de lege ferenda
Keywords: management; LLC; liability